MEDIATING ROLE OF TRUST ON VISIT INTENTION: MUSLIM FRIENDLY TOURISM IN TANA TORAJA - Fasiha, Fasiha; Hamida, Ambas; Jabani, Muzzayanah; Rusli, Muhammad (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study evaluated the relationship between attitudes, subjective norms and perceived behavior control by using visit intention as a moderating variable and trust as a mediating variable. This study used quantitative research. The population in this study were Muslim tourists who visited tourist attractions in Tana Toraja district. Sampling used a purposive sampling with certain criteria. Data collection techniques used a questionnaire method. Meanwhile, data analysis in this study used SEM PLS. The results showed that a comprehensive trust mediation was found in the perception relationship between behavioral control and visit intention for Muslim-friendly tourism behavior, while in the attitude relationship, subjective norms toward visit intention Muslim-friendly tourism were found to be partial mediation. In other words, the model proposed to form a fundamental change in the visiting intention pattern of Muslim-friendly tourism for tourists was not running optimally. However, this study still finds it important that trust is able to mediate the relationship between perceptions of behavior control and visit intention in Muslim-friendly tourism. This research had two contributions, namely empirical evidence and policy. The results of this study were additional literature related to evidence of the development of the Muslim-friendly tourism trust on visit intention model. In addition, the results of this study helped the tourism agency achieve sustainable development